The Upper Miocene fossil fish locality of Pecetto di Valenza (Piedmont, Italy): a multidisciplinary approach - Gaudant J.; Courme Rault M. D; Fourtanier E.; FORNACIARI, ELIANA (2010)
Pecetto di Valenza is the first Upper Miocene fossil fish locality of Piedmont to have been studied and the only one in which fossils are embedded in a diatomitic sediment. Sturani & Sampo (1973) considered that it is Messinian in age. However, as a preliminary examination of the diatomflora from this locality by one of us (Elisabeth Fourtanier) suggested a late Tortonian age, it was decided to complete a more thorough micropalaeontological study in order to clarify the stratigraphical question. A comprehensive study of the diatom flora confirmed the preliminary results. Later; the study of the calcareous nannoplankton also concluded a late Tortonian age for the fossiliferous diatomaceous sediment. However, the examination of the planktonic foraminifera supports a Messinian correlation. Such a contradiction is puzzling and is hitherto not understood, even when making reference to a possible reworking. The composition of the fish fauna from Pecetto di Valenza is very similar to that observed in the two other marine Upper Miocene fish faunas of Piedmont, as myctophids predominate in all of them with more than 50% of the total number of specimens, whereas clupeids belonging to the species Alosa elongata comprise about 20% of the fauna. Except for the two species of the genus Lepidopus which, together; reach almost 8%, each one of the other identified taxa is below 5% of the fish fauna. The occurrence of upwellings, which is indicated by the abundance of the diatom Thalassionema nitzchioides in every diatomaceous sample, may have been responsible for the rather significant percentage of Lepidopus in the fish fauna. However, the upwelling environment did not exert any notable influence on the overall composition of the fish fauna from Pecetto di Valenza, relatively to those of the Tortonian of the Tanaro River and of the pre-evaporitic Messinian of Roddi, two localities in which diatoms are missing.